Analysis of the Comfort Level of Green Open Spaces in Medan - Srena, Mona Fhitri; Alfi Laila Zuhriansah; Kusuma, Yosie Syadza; Ria Astuti; Rizky Febriana Br Lubis; Rahmah, Hanifa; Sidabukke, Simon H (Jurnal Biologi Tropis, 2025)
Urban environmental comfort increasingly challenged by rapid population growth and development. Green Open Spaces (GOS) are crucial in enhancing community also life quality. This study assess the comfort value of GOS in Medan City by examining physical, biotic, and social factors. The research employed a combination of vegetation inventory to evaluate biodiversity, environmental measurements to assess air quality and noise levels, and public perception surveys to understand social comfort. The findings reveal that Cadika Park possesses the highest vegetation diversity with 31 tree species, dominated by Terminalia mantaly, which also recorded the highest Leaf Area Index (LAI) of 1.78. Physically, air quality within GOS areas is better than outside, although noise levels still exceed environmental quality standards. Socially, the community perceives GOS as comfortable and beneficial for daily activities. In conclusion, despite certain physical limitations, GOS in Medan City contributes positively to environmental comfort, underscoring the need for continuous management and sustainable development of urban green spaces.